Mathematical interpretation of wave propagation, standing wave resonance, and absorption in a metasurface absorber - Nilotpal; Bhattacharyya S.; Chakrabarti P. (My University, 2025)
We propose a mathematical model of multiple interference phenomena occurring inside the dielectric cavity of the metasurface absorber. Subsequently, it derived the expressions for electric and magnetic fields within the structure. The model enables one to mathematically interpret wave propagation, standing wave formation, and absorption in terms of electric and magnetic fields. We also discussed the effect of change in the polarization angle of the incident electromagnetic wave on the standing wave pattern and surface-current orientation. The study reveals that the theory is equally applicable for transverse electric and transverse magnetic polarized incident waves. All the mathematical aspects of the theory have been analytically established through the validation of simulation data. It has been found that the theory is in good agreement with the analytically obtained results. © 2020 Society of Photo-Optical Instrumentation Engineers (SPIE).